GONDANG BATAK TOBA PADA PESTA PERNIKAHAN MASYARAKAT JAWA DI KABUPATEN ASAHAN (STUDI TERHADAP FUNGSI DAN MAKNA GONDANG BATAK) - Tamba, Lambertus (Universitas Negeri Medan, 2013)
This study aims to determine the factors that cause Gondang Batak Toba used in Javanese wedding in Asahan District, to determine the presentation of the Toba Batak Gondang Javanese wedding ceremony in Asahan District, and to know the functions and Meaning Gondang Batak Toba in Javanese wedding ceremony in Asahan.In this study, the deepening of discussions Gondang writing Batak Toba, music theory, form of presentation, concept shape theory, theory of functions and meanings.The metode in this study uses a qualitative description method. Location of the study was conducted in Asahan area.In the present study found that the form of presentation of the data at this party Gondang Batak used after the event is finished izab. ie at the time of the event manortor and entertainment events. Functions and Gondang here used as entertainment, because the functions held are no longer used as a means of culture that is traditional, which typically has a sacred values ‹‹when its use as used in Javanese wedding. 're Right Gondang meaning in this event only as a means of connecting the social interaction between ethnic Batak and Javanese.